2020
DOI: 10.18632/aging.103222
|View full text |Cite|
|
Sign up to set email alerts
|

Tomatidine suppresses inflammation in primary articular chondrocytes and attenuates cartilage degradation in osteoarthritic rats

Abstract: In this study, we investigated whether the anti-inflammatory effects of tomatidine alleviate osteoarthritis (OA)-related pathology in primary articular chondrocytes and a rat OA model. STITCH database analysis identified 22 tomatidine-target genes that were enriched in 78 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. Moreover,39 of the 105 OA-related KEGG pathways were related to tomatidine-target genes. The top two OA-related KEGG pathways with tomatidine-target genes were the MAPK and neutrophin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In contrast, the systemic knockout of ALPK1 probably breaks the dynamic equilibrium of osteoblasts and osteoclasts in the subchondral bone, although alleviation of cartilage degradation arises. Similarly, Chu and colleagues ( 42 ) discovered that the systemic administration of tomatidine via drinking attenuated cartilage degradation in rats with OA, without improving the destruction of the subchondral bone in the tibia.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, the systemic knockout of ALPK1 probably breaks the dynamic equilibrium of osteoblasts and osteoclasts in the subchondral bone, although alleviation of cartilage degradation arises. Similarly, Chu and colleagues ( 42 ) discovered that the systemic administration of tomatidine via drinking attenuated cartilage degradation in rats with OA, without improving the destruction of the subchondral bone in the tibia.…”
Section: Discussionmentioning
confidence: 96%
“…Tomatidine is thought to attenuate the inflammatory response in LPS-induced macrophages and articular chondrocytes [12,20]. Previous studies have demonstrated that tomatidine can induce apoptosis effects in osteosarcoma, lung cancer, and breast cancer [11,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Kozukue et al [ 12 ] reported on the analysis of the tetrasaccharide glycoalkaloids α-tomatine and dehydrotomatine as well the corresponding aglycones tomatidine and tomatidenol lacking the carbohydrate side chain, as illustrated in Figure 2 of vegetative parts (calyxes, flowers, green and red tomato fruit, leaves, roots and stems) of greenhouse-grown cherry (mini) and two standard tomatoes using HPLC and mass spectrometry. The analytical method for tomatidine is of interest because it can be used in metabolism and pharmacology studies of reported beneficial biological properties, including anti-trichomonad [ 4 ], antiviral [ 13 ], anti-inflammatory [ 14 ], and anti-cancer effects [ 15 ]. Friedman et al [ 16 ] reported on the analysis of peel powders from six commercial cherry tomato varieties for free amino acid, phenolic, flavonoid, β-carotene, lycopene, and glycoalkaloid content using HPLC/MS (mass spectrometry).…”
Section: Discussionmentioning
confidence: 99%